2006
DOI: 10.1111/j.1471-4159.2006.03709.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion interaction at the pore of Lc‐type Ca2+ channel is sufficient to mediate depolarization‐induced exocytosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 67 publications
8
62
0
Order By: Relevance
“…Indeed, our present findings showed a larger latency when Ba 2+ substituted for Ca 2+ , consistent with previous findings by Wang et al 35 However, a significant shorter delay was observed also in La 3+ , despite its impermeability and having no effect on either [La 3+ ] i or [Ca 2+ ] I . 11 Furthermore, when either intracellular Ca 2+ or Sr 2+ was elevated by ionophore the kinetics of the fusion pore was virtually identical. The insensitivity of the fusion pore to the type of the cytosolic cation stands in marked contrast to changes in fusion pore kinetics observed by the extracellular ion binding at the channel.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Indeed, our present findings showed a larger latency when Ba 2+ substituted for Ca 2+ , consistent with previous findings by Wang et al 35 However, a significant shorter delay was observed also in La 3+ , despite its impermeability and having no effect on either [La 3+ ] i or [Ca 2+ ] I . 11 Furthermore, when either intracellular Ca 2+ or Sr 2+ was elevated by ionophore the kinetics of the fusion pore was virtually identical. The insensitivity of the fusion pore to the type of the cytosolic cation stands in marked contrast to changes in fusion pore kinetics observed by the extracellular ion binding at the channel.…”
Section: Discussionmentioning
confidence: 86%
“…These results further confirm La 3+ exclusion from entry into chromaffin cell, during depolarization consistent with previous studies. 11,22 'Foot' parameters are affected by the charge carrier cations. In chromaffin cells, amperometric spikes recorded during membrane depolarization are often preceded by a pre-spike current event ('foot') corresponding to the open state of the fusion pore.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, L-type channels can be up-and down-modulated by secreted products through the activation of -adrenergic autoreceptors (Hernandez-Guijo et al 1999;Cesetti et al 2003) and play a regulatory function in the depolarization-evoked exocytosis in chromaYn cells Nagy et al 2004). Fourth, recent data suggest an additional role for L-type channels, which can act as Ca 2+ sensor proteins in neuroendocrine secretion (Lerner et al 2006). The occupancy of L-type channel pore by an impermeable cation, such as La 3+ , lead to a conformational change that is transmitted to the exocytotic machinery upstream of intracellular Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%